A multicentre, randomized, single‐blind comparison of topical clindamycin 1%/benzoyl peroxide 5% once‐daily gel versus clindamycin 1% twice‐daily gel in the treatment of mild to moderate acne vulgaris in Chinese patients. (13th April 2016) - Xu, J.H.; Lu, Q.J.; Huang, J.H.; Hao, F.; Sun, Q.N.; Fang, H.; Gu, J.; Dong, X.Q.; Zheng, J.; Luo, D.; Li, F.Q.; Wang, G.; et al.
Abstract: Background: Acne vulgaris affects up to 54% of Chinese adolescents. Combination therapy has become the recommended standard of care for acne. Objective: The aim of this study was to compare the efficacy and safety of clindamycin (1%) and benzoyl peroxide (5%) (CDP/BPO) gel once daily vs. clindamycin (1%) (CDP) monotherapy gel twice daily in Chinese patients with mild to moderate acne. Methods: 1020 patients (aged 12–45 years) with mild to moderate acne were randomized (1 : 1); 1016 patients were treated with CDP/BPO ( n = 500) or CDP ( n = 516) for a 12‐week treatment period. Efficacy assessments were performed at baseline, and at weeks 1, 2, 4, 8 and 12; and primarily included change in total lesion count (inflammatory and non‐inflammatory lesions), and proportion of patients with a minimum 2‐grade improvement in Investigator's Static Global Assessment (ISGA) score. Patient safety and local tolerability were also evaluated. Results: Patients in CDP/BPO group showed a greater per cent reduction in total lesion count compared with patients in CDP group at week 12 (delta = −0.05; 95% CI = −0.09, −0.02; P = 0.003); statistically significant reduction in lesion count was noted as early as week 1 and continued through week 12. A greater proportion of patients in CDP/BPO group showed a ≥2‐grade improvement in ISGA score at week 12 compared with CDP group (30.2% vs. 22.7%; P = 0.018). Overall, the incidence of adverse events (AEs) was higher in the CDP/BPO group (14.4%) than in the CDP group (7.9%); the most commonly reported events were generally related to application site reactions (erythema, pruritus and swelling). Incidence of drug‐related AEs was 8.6% in CDP/BPO group and 1.2% in CDP group. Both groups showed trends towards reduction in investigator and subject rated local tolerability scores. Conclusion: CDP/BPO gel demonstrated superior efficacy over CDP gel along with acceptable safety and tolerability in Chinese patients with mild to moderate acne. Clinical Trials.gov number: NCT01915732: